The Concept of Technical Inheritance in Operation: Analysis of the Information Flow in the Life Cycle of Smart Products. (2016) - Demminger, Christian; Mozgova, Iryna; Quirico, Melissa; Uhlich, Florian; Denkena, Berend; Lachmayer, Roland; Nyhuis, Peter
Abstract: Industry 4.0 opens great potentials in productions technologies by establishing communication between machines and equipment as well as processes along the life cycle of products. Within the Collaborative Research Center (CRC) 653 several aspects of the design and application of communicative and intelligent systems and components are demonstrated. The CRC aims to enable smart products, so-called gentelligent components, to give feedback to the product and production processes based on inherently stored information. This work continues a series of publications regarding the development of the concept of Technical Inheritance. Here, the process of Technical Inheritance is applied to improve gentelligent components. This was realized according to the biological principle to transfer hereditary information on the basis of evolutionary mechanisms and variations of the information transfer. To provide an efficient information management throughout the life cycle of components and to transfer relevant information from the current generation of the component to the next generation a unified closed data exchange format GIML was developed. At the example of a load-sensitive magnesium wheel carrier of the racing car RP09 this approach is demonstrated: the information flows over the life cycle are analyzed, the concept of Technical Inheritance applied and its advantages discussed.